The scale dependence of fungal community distribution in paddy soil driven by stochastic and deterministic processes. (December 2019) - Zhao, Jianshu; Gao, Qun; Zhou, Jizhong; Wang, Mengmeng; Liang, Yuting; Sun, Bo; Chu, Haiyan; Yang, Yunfeng
Abstract: Fungal communities play important roles in terrestrial ecosystem functioning. Unraveling the relative importance of stochastic versus deterministic processes in shaping biogeographic patterns of fungal communities has long been a challenge in microbial ecology, owing to high biodiversity and difficulties in identifying fungal taxa. Using a unique anthropogenic system of geographically isolated paddy 'islands', we collected 198 soil samples with a spatially explicit design to examine how ecological processes shaped fungal biogeographic patterns. Fungal community structure showed scale-dependent distance-decay relationships. Stochastic processes (dispersal and drift) contributed more to community assembly than deterministic processes (selection) at the local scale, which was largely attributed to drift. In contrast, deterministic processes contributed more to community assembly than stochastic processes at the regional scale, with soil dissolved organic carbon being the most important measured factor. Collectively, scale dependence of fungal biogeographical patterns in paddy soils is influenced by differential contribution of deterministic and stochastic processes.